Taking College Teachers' Working Conditions Seriously: Adjunct Faculty and Negotiating a Labor-based Conception of Quality. (15th April 2020) - Rhoades, Gary
ABSTRACT: This study takes college teaching/educational quality seriously by taking teachers' working conditions seriously. Data consist of contractual provisions about adjunct faculty members' access to instructional resources and professional development in 254 collective bargaining agreements. The research analyzes the negotiated balance in quality-related working conditions between professional rights and managerial discretion, stratified access to those working conditions in the collectively negotiated jurisdiction between part- and full-time faculty, as well as explicit references to educational quality and/or public benefits/beneficiaries. The findings indicate gains in adjunct faculty rights/voice, some parity with full-time faculty in quality-related working conditions, and some explicit references to quality/public benefits. But they also speak to considerable managerial discretion in not providing those conditions, and adjunct faculty's lesser access to them. The research builds on and extends literature on academic employees' working conditions, finding value in a labor-based conception of basic, quality-related working conditions, and in conceptualizing professorial stratification as fluid, contingent, and shaped by collectively negotiated jurisdiction. It also points to the feasibility of enhancing adjunct faculty working conditions by linking them to higher education attending more to educational quality and public purpose in better serving students and society.